AN EVALUATION OF POSTOPERATIVE ANALGESIC EFFECT OF TRANSVERSUS ABDOMINIS PLANE BLOCK IN COMPARISON TO INTRAVENOUS DICLOFENAC SODIUM IN TOTAL ABDOMINAL HYSTERECTOMY SURGERIES: A PROSPECTIVE RANDOMIZED STUDY - Dr. Susmita Sarangi; Dr Shah Raj Jayantilal; Dr. Dipali Taneja; Dr. Shrikanta (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Effective postoperative pain management is essential in enhancing recovery and reducing morbidity after lower abdominal surgeries such as Total Abdominal Hysterectomy (TAH). The Transversus Abdominis Plane (TAP) block is a technique of regional anesthesia that is increasingly used to control postoperative pain. This study aimed to compare the efficacy of ultrasound-guided TAP block with intravenous Diclofenac sodium for postoperative analgesia in TAH.Methods: Thirty ASA Grade I–II female patients aged 30–60 years undergoing elective TAH under spinal anesthesia were randomized into two equal groups. Group T received bilateral ultrasound-guided TAP block with 15 ml of 0.25% Bupivacaine on each side, while Group D received intravenous Diclofenac sodium (1 mg/kg) on demand. Pain was assessed using the Visual Analog Scale (VAS) at 0, 2, 4, 6, 12, and 24 hours. Secondary parameters included time to first rescue analgesia, total analgesic requirement, hemodynamic changes, and adverse events.Results: VAS scores were significantly lower in Group T at all time points from 2 hours onward (p < 0.05). Group T showed longer time to first rescue analgesia (11.40 ± 0.74 vs. 2.93 ± 1.03 hours; p < 0.01) and reduced total analgesic consumption (105.00 ± 38.03 vs. 205.00 ± 34.33 mg; p < 0.01). Hemodynamic parameters were more stable in the TAP group. No major complications were observed.Conclusion: TAP block provides superior and prolonged postoperative analgesia compared to intravenous Diclofenac in TAH and is a safe and effective analgesic technique.